Experiences of Weight-Loss Surgery in People With Serious Mental Illness: A Qualitative Study - Every-Palmer, Susanna; Romans, Sarah E.; Stubbs, Richard; Tomlinson, Anneka; Gandhi, Sophie; Huthwaite, Mark (Frontiers in Psychiatry, 2020)
Background: Bariatric surgery is seldom accessed by people with serious mental illness, despite high rates of obesity in this population. It is sometimes assumed that patients with complex psychiatric histories will have poor post-surgical weight loss or exacerbation of psychiatric symptoms, although this is unsubstantiated. Objectives: A qualitative descriptive study to explore personal experiences and the impact of bariatric surgery on physical and mental well-being and life-quality in individuals with serious mental illness. Methods: Nine adults with a history of bariatric surgery and concurrent severe depressive disorder, bipolar disorder or schizoaffective disorder were interviewed about their experiences of bariatric surgery and its outcomes using semi-structured interview schedules. Data were transcribed and inductive thematic analysis undertaken. Results: Five broad themes emerged: (1) surgery was highly effective for weight loss, and resulted in subjective improvements in physical health, quality of life and mental health described as being able to live a life; (2) recovering from surgery was a tough road, notably in the post-operative period where negative sequelae often anteceded benefits; (3) post-operative support was important, but sometimes insufficient, including from families, mental health services and surgical teams; (4) most considered surgery life-changing, recommending it to others with mental illness and obesity, two had different experiences; (5) participants considered it discriminatory that people with mental illness were not referred or declined weight loss surgery. Conclusions: Participants benefited from bariatric surgery and felt it should be offered to others with mental illness, but with additional care and support. Keywords: mental illness, psychosis, obesity, bariatric surgery, qualitative research, stigma and discrimination Acknowledgements: We thank those people who generously gave their time to participate in this study. Funding: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.